Daily field checking list by Walter Rosene, February 18, 1940 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Robert Walker, February 18, 1940. Also notes the birds were very scarce. Plustek--flatbed